Restorative Justice dalam KUHP Baru: Antara Kepastian Hukum dan Diskresi Aparat Penegak Hukum - Heri Purnomo; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Restorative justice has emerged as an alternative approach to resolving criminal cases, emphasizing the restoration of relationships among the offender, the victim, and the community. The reform of the Criminal Procedure Code (KUHAP) presents a strategic opportunity to integrate restorative justice as a new paradigm for criminal case resolution, particularly during the police investigation stage. This study aims to analyze the urgency of embedding restorative justice within the new Criminal Procedure Code to establish a legal basis for police authority and to assess its implications for Indonesia's criminal justice system. The research employs a normative-juridical method, utilizing both statutory and conceptual approaches. The findings indicate that incorporating restorative justice into the new Criminal Procedure Code is essential to provide clear legal legitimacy for restorative case resolution practices, prevent policy fragmentation among law enforcement agencies, and foster the realization of substantive, restoration-oriented justice.